Tyrosine Kinases as Druggable Targets in Cancer - Ren, Huan (IntechOpen, 2019)
Protein tyrosine kinase (PTK) deregulation contributes to growth of cancer and many other diseases. The development of small-molecule tyrosine kinase inhibitors (TKIs) that target the deregulated PTKs, such as epidermal growth factor receptor (EGFR) in non-small-cell lung cancer (NSCLC) and Bcr-ABL in chronic myeloid leukemia (CML), has revolutionized disease management. In this book, we examine a few aspects of PTKs and cancer, considering efficacy, predictive markers to therapeutic response, limitations, and future directions in TKI treatment. In this rapidly evolving field, overcoming therapeutic resistance is most challenging, and multi-targeting directs the next-generation TKIs and combination therapy as ongoing strategies in cancer treatment.